Influence of Aloe Arborescens Mill. extract on selected parameters of pro-oxidant-antioxidant equilibrium and cytokine synthesis in rowers - Basta, P.; Pilaczynska-Szczesniak, L.; Woitas-Slubowska, D.; Skarpanska-Stejnborn, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
This investigation examined the effect of supplementation with Biostimine, extract from aloe arborescens Mill. leaves, on the levels of pro-oxidant-antioxidant equilibrium markers and anti- and proinflammatory cytokines in rowers subjected to exhaustive exercise. This double-blind study included 18 members of the Polish Rowing Team. Subjects were randomly assigned to the supplemented group (n = 9), which received one ampoule of Biostimine once daily for 4 weeks, or to the placebo group (n = 9). Subjects performed a 2,000-meter-maximum test on a rowing ergometer at the beginning and end of the preparatory camp. Blood samples were obtained from the antecubital vein before each exercise test, 1 min after completing the test and after a 24-hr recovery period. Superoxide dismutase and glutathione peroxidase activity as well as the concentration of thiobarbituric acid reactive substances (TBARS) were assessed in erythrocytes. In addition, total antioxidant capacity (TAC) and creatine kinase activity were measured in plasma samples, and cytokine (IL-6, IL-10) concentrations were determined in the serum. Before and after Biostimine supplementation, exercise significantly increased the values of SOD, IL-6, IL-10, and TBARS in both groups. However, postexercise and recovery levels of TBARS were significantly lower in athletes receiving Biostimine than in controls. After supplementation, TAC was the only variable with the level being significantly higher in the supplemented group than in the placebo group. Consequently, we can conclude that Biostimine supplementation reduces the postexercise level of TBARS by increasing the antioxidant activity of plasma but has no effect on inflammatory markers.